2000
DOI: 10.1097/00005237-200003000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Discharge Assessment of the Medically and Socially High-Risk Infant

Abstract: Discharge from a neonatal intensive care unit (NICU) requires assessment, coordination, and possible intervention by a multidisciplinary team. The infant's health condition and the family's social situation must be considered before discharge to design a discharge plan for the child's long-term well-being. This article presents the neonatal discharge assessment tool (N-DAT) as a method to identify risks at the time of discharge. The tool offers specific recommendations for use with infants who are medically or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 7 publications
0
57
0
3
Order By: Relevance
“…24 Additionally, the medical home must be contacted before discharge so that pertinent information is relayed and the infant is appropriately scheduled for follow-up. 39,43 Poor communication between the NICU and the medical home threatens parental trust and may compromise care. 34,44,45 Finally, mistrust of providers associated with child protective services needs to be addressed to remove barriers to addressing social determinants of health.…”
Section: Homementioning
confidence: 99%
“…24 Additionally, the medical home must be contacted before discharge so that pertinent information is relayed and the infant is appropriately scheduled for follow-up. 39,43 Poor communication between the NICU and the medical home threatens parental trust and may compromise care. 34,44,45 Finally, mistrust of providers associated with child protective services needs to be addressed to remove barriers to addressing social determinants of health.…”
Section: Homementioning
confidence: 99%
“…Important criteria for discharge of preterm infants include (1) medically stable, (2) parents are informed about and capable of infant care, (3) parents are emotionally ready for their parental roles, (4) home care services are offered for the infants' continuing health problems, (5) a follow-up plan for infants, and (6) parents have sufficient sources of financial and social support (Forsythe et al, 2007;Griffin & Abraham, 2006;Robison, Pirak, & Morrell, 2000). However, some studies have shown that these factors are not taken into consideration while planning discharges for preterm infants (Griffin & Abraham, 2006;Mancini & While, 2001;Smith, Dukhovny, Zupancic, Gates, & Pursley, 2012).…”
Section: Healthcare System-related Risk Factorsmentioning
confidence: 99%
“…Early discharge of preterm infants is sometimes implemented to reduce hospital costs (Richardson et al, 2001), provide more efficient use of hospital beds, avoid the risk of nosocomial infection, and shortening the length of parentinfant separation (Lian, Ying, Peng, & Yann, 2008). Within this context, prior to the discharge of preterm infants from the intensive care unit, healthcare professionals should inclusively assess the medical features of the infant and parental-social risk factors, should offer extensive and effective discharge service in accordance with the necessities of those infants and parents, and create a follow-up plan for the postdischarge (American Academy of Pediatrics [AAP], 2008; Robison et al, 2000). Within this context, prior to the discharge of preterm infants from the intensive care unit, healthcare professionals should inclusively assess the medical features of the infant and parental-social risk factors, should offer extensive and effective discharge service in accordance with the necessities of those infants and parents, and create a follow-up plan for the postdischarge (American Academy of Pediatrics [AAP], 2008; Robison et al, 2000).…”
Section: Healthcare System-related Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations